The use of Medicinal Plants for the treatment of Gonorrhoea and Syphilis in South West Bengal of India - Dulal Chandra Das; Nirmalya Kumar Sinha; Jadab Chandra Chattopadhyay; Monalisa Das; Pradip Samanta (International Journal of Phytomedicine, 2013)
Gonorrhoea and Syphilis as Sexually Transmitted Infections occur throughout the world. In India the prevalence of these diseases are in alarming situation due to the rapid spread of the diseases, high cost of treatment and the increased risk of transmission. Current therapies available for symptomatic treatment are quite expensive beyond the reach of common people and associated with the emergence of drug resistance. Many patients seeking help from the alternative systems of medicines for treatment. In our country several crude plants are used as medicine since Vedic period. Herbal medicines provide rational means for the treatment of many Sexually Transmitted Infections. The herbal medicines have many advantages: have no side effects, better patient tolerance and relatively less expensive. Locally available herbal practitioners or healers have practiced since past in this direction. Furthermore the acceptability of herbal medicines are greater to control these infections due to the social stigma associated with them and in case of women it is much more acceptable to discuss their problem with the traditional healers or herbal medical practitioners. In the present study thirty seven medicinal plants have been recorded for the treatment of Gonorrhoea and Syphilis and documented from South West Bengal of India.